The effects of 3D sound in a 360-degree live concert video on social presence, parasocial interaction, enjoyment, and intent of financial supportive action. Issue 126 (June 2019) - Shin, Mincheol; Song, Stephen W; Kim, Se Jung; Biocca, Frank
Highlights: 3D sound enhances social presence. 360-degree stereoscopic visualization also enhances social presence. Social presence affects parasocial interaction and enjoyment directly. Auralization indirectly affects support provision through social presence. Parasocial interaction plays a pivotal role in predicting support provision. Abstract: What would be the social consequences of rendering three-dimensional (3D) sound in a pre-recorded live concert video? Although previous studies demonstrate that the rendering of 3D sound in a pre-recorded live concert may foster a sense of presence, whether and how 3D sound will affect audience's experiences beyond the reporting of a sense of presence has yet to be elucidated. To further investigate the socio-psychological impact of 3D sound in a pre-recorded live concert content, a 2 × 2 mixed design experiment ( N = 44), having sound as a within factor (2D vs. 3D) and visualization display mode as a between factor (monoscopic TV vs. stereoscopic VR), was conducted. Drawing from the social presence theory and related work, we specifically investigated whether 3D sound in a pre-recorded live concert content, rendered either through a monoscopic TV screen or a stereoscopic VR device, will contribute to enhancing audience's sense of being with a performer (i.e., social presence), and whether this will subsequently influence audience's psychological engagement with the performer (i.e., parasocial interaction), enjoyment as need satisfaction, and intent of financial supportive action towards the performer. Results showed that 3D sound enhanced a sense of social presence, and this, in turn, positively influenced parasocial interaction and enjoyment. In addition, parasocial interaction, fostered by social presence, positively affected audience's intent of financial supportive action. Further implications of the findings with respect to the role of 3D sound in a pre-recorded live concert content, rendered through a VR technology, are discussed.